Perancangan UI/UX Website Point of Sale (POS) Menggunakan Metode Design Thinking di PT Hayaa Investama Group - Naesya Azzahra; Pradita Eko Prasetyo Utomo; Muhammad Razi A. (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The process of managing sales transactions, inventory, and financial records at PT Hayaa Investama Group is still done manually. This causes the work process to be less efficient and risks causing recording errors. This condition indicates the need for the implementation of a web-based Point of Sale (POS) system that can support the company's operational activities more effectively, especially in terms of ease of use. This study aims to design the interface and user experience of the web-based Point of Sale system at PT Hayaa Investama Group using the Design Thinking method. This method is implemented through five stages, namely Empathy, Definition, Ideation, Prototype, and Testing. Data collection was carried out through observation and interviews with employees and company owners to obtain an overview of user needs. The result of this study is a High-Fidelity prototype equipped with features for managing transactions, inventory, suppliers, purchases, sales, and reports. Prototype testing was conducted using Maze Usability Testing and resulted in a score of 80% from 9 respondents with 7 block missions. The test results indicate that the developed system design is quite easy to use and can be understood by users